2014
DOI: 10.3164/jcbn.13-90
|View full text |Cite
|
Sign up to set email alerts
|

Supplementation of parenteral nutrition with fish oil attenuates acute lung injury in a rat model

Abstract: Fish oil rich in n-3 polyunsaturated fatty acids has diverse immunomodulatory properties and attenuates acute lung injury when administered in enternal nutrition. However, enteral nutrition is not always feasible. Therefore, we investigated the ability of parenteral nutrition supplemented with fish oil to ameliorate acute lung injury. Rats were infused with parenteral nutrition solutions (without lipids, with soybean oil, or with soybean oil and fish oil) for three days. Lipopolysaccharide (15 mg/kg) was then … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 39 publications
1
3
0
Order By: Relevance
“…Supporting our findings, FO emulsion preconditioning for 3 days was previously found to significantly lower the serum and lung levels of TNF-α, IL-1β and IL-6 in an ischemia-reperfusion ALI model in rats [29]. Clinoleic or Omegaven preconditioning also reduced TNF-α in BALF in the present study, similar to previous findings from humans [7], rats [19,29] and mice [30,31], indicating that infusion of FO achieved a significant reduction of TNF-α upon ALI induction.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Supporting our findings, FO emulsion preconditioning for 3 days was previously found to significantly lower the serum and lung levels of TNF-α, IL-1β and IL-6 in an ischemia-reperfusion ALI model in rats [29]. Clinoleic or Omegaven preconditioning also reduced TNF-α in BALF in the present study, similar to previous findings from humans [7], rats [19,29] and mice [30,31], indicating that infusion of FO achieved a significant reduction of TNF-α upon ALI induction.…”
Section: Discussionsupporting
confidence: 92%
“…Prostaglandins and leukotrienes are known potent inflammatory lipid mediators that are involved in hypersensitivity and respiratory disorders, and have immunoregulatory properties [19,20]. AA is metabolized to produce proinflammatory series 4 leukotrienes and series 2 prostaglandins.…”
Section: Discussionmentioning
confidence: 99%
“…One of the potential mechanisms of adjunctive efficacy is the modulation of gut microbiota by specific dietary supplementation (Singh et al 2017 ). ω-3 PUFAs supplementation has a therapeutic benefit in alleviating several lung disorders, including COPD (Wood 2015 ), asthma (Bisgaard et al 2016 ), ARDS (Kohama et al 2014 ), and even coronavirus disease COVID-19 (Safaei Ardestani & Rahideh 2022 ). However, the influence of ω-3 PUFAs supplementation on PM2.5 exposure induced lung injury remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Fish oil was found to have anti-inflammatory and pro-resolving effects on lung injury when compared to long-chain triglycerides (LCT) or medium-chain triglycerides (MCT)/LCT emulsions, indicating that partial replacement of n-6 fatty acids with marine n-3 fatty acids during ARDS may be beneficial. In a rat model of acute lung injury, Kohama et al ( 2014 ) found that, when compared to soybean oil, parenteral nutrition supplemented with fish oil improved gas exchange and inhibited both neutrophil recruitment and upregulation of inflammatory mediator mRNAs, as well as increased anti-inflammatory eicosanoid 4-series leukotrienes (LTB5) production.…”
Section: Discussionmentioning
confidence: 99%